Perception or Capabilities? An Empirical Investigation of the Factors Influencing the Adoption of Social Media and Public Cloud in German SMEs - Sohaib S. Hassan; Christian Reuter; Levan Bzhalava (World Scientific Publishing Co. Pte Ltd, 2022)
Social media and public cloud computing (SM&PC) have emerged as important resources of small and medium enterprises (SMEs), but not all SMEs use SM&PC. The existing research predominantly focuses on the role of either the features of social media and cloud computing in relation to the perceptions of decision makers or the internal capabilities of organization concerning new innovation adoption. By integrating multidisciplinary literature, we, instead, argues that both the perception- and capability-related factors could play an important role in the adoption of new ICT technology, such as SM&PC. Therefore, we empirically investigated the decision maker’s perception-related and SME’s capability-related factors that may influence the adoption of SM&PC in SMEs in Germany. We used quantitative research methods to examine the proposed hypotheses on a sample of 2,404 SMEs from 17 industrial sectors. The results demonstrate that the decisions of German SMEs to engage in social media and cloud computing are not only influenced by the perceptions of SME owners about the usefulness, security aspects, and the implementation costs of SM&PC, but also by the internal capabilities of an SME, namely the innovativeness of an SME. The results and potential contributions of our research are discussed.